Rhetoric in legislative bargaining with asymmetric information - Ying Chen; Hülya Eraslan (The Johns Hopkins University, Department of Economics, 2010)
In this paper we analyze a legislative bargaining game in which parties privately informed about their preferences bargain over an ideological and a distributive decision. Communication takes place before a proposal is offered and majority rule voting determines the outcome. When the private information pertains to the ideological intensities but the ideological positions are publicly known, it may not be possible to have informative communication from the legislator who is ideologically distant from the proposer, but the more moderate legislator can communicate whether he would 'compromise' or 'fight' on ideology. If instead the private information pertains to the ideological positions, then all parties may convey whether they will 'cooperate', 'compromise', or 'fight' on ideology. When the uncertainty is about ideological intensity, the proposer is always better off making proposals for the two dimensions together despite separable preferences, but when the uncertainty is about ideological positions, bundling can result in informational loss which hurts the proposer.
Keywords: C78; D72; D82; D83; 330; Politische Entscheidung; Parlament; Asymmetrische Information; Abstimmungsregel; Verhandlungstheorie; Public Choice; Theorie